2012
DOI: 10.1016/j.ydbio.2012.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Ring1a/b polycomb proteins regulate the mesenchymal stem cell niche in continuously growing incisors

Abstract: Rodent incisors are capable of growing continuously and the renewal of dental epithelium giving rise to enamel-forming ameloblasts and dental mesenchyme giving rise to dentin-forming odontoblasts and pulp cells is achieved by stem cells residing at their proximal ends. Although the dental epithelial stem cell niche (cervical loop) is well characterized, little is known about the dental mesenchymal stem cell niche. Ring1a/b are the core Polycomb repressive complex1 (PRC1) components that have recently also been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 46 publications
1
52
0
9
Order By: Relevance
“…Specifically, deletion of Bmp2 in osterixpositive mesenchymal progenitor cells causes abnormal odontoblast differentiation and short roots (Rakian et al, 2013). Moreover, restriction of Bmp4 expression in the dental mesenchyme by Ring proteins, which contain a characteristic zinc-finger domain that mediates protein-protein interactions, affects odontoblast differentiation and root formation (Lapthanasupkul et al, 2012). To date, however, the precise regulatory function of mesenchymal Bmp signaling during root development remains unclear.…”
Section: Bmp/tgfβ Signalingmentioning
confidence: 99%
“…Specifically, deletion of Bmp2 in osterixpositive mesenchymal progenitor cells causes abnormal odontoblast differentiation and short roots (Rakian et al, 2013). Moreover, restriction of Bmp4 expression in the dental mesenchyme by Ring proteins, which contain a characteristic zinc-finger domain that mediates protein-protein interactions, affects odontoblast differentiation and root formation (Lapthanasupkul et al, 2012). To date, however, the precise regulatory function of mesenchymal Bmp signaling during root development remains unclear.…”
Section: Bmp/tgfβ Signalingmentioning
confidence: 99%
“…Others also found that failure in S-phase entry, proliferative arrest and p21 upregulation in Ring1/Rnf2 double mutant cells [236]. In vivo studies found that Bmp signaling is altered in the mandibular molar of Ring1 −/− ; Rnf2 cko/cko mice [237].…”
Section: Core Members Of Ncprcsmentioning
confidence: 96%
“…This rapidly dividing population in the incisor represents the cells that differentiate, and thus the transition from a slow-cycling stem cell to a rapidly cycling progenitor is a critically important yet poorly understood process. The transit-amplifying cells are the most rapidly cycling cells in the incisor pulp and they are located immediately distal to the slowcycling stem cells (Lapthanasupkul et al, 2012). These cells express specific genes, most notably those of the polycomb repressive complex 1 (Prc1), that are generally not expressed in the surrounding cells and which are important for cell proliferation (Lapthanasupkul et al, 2012).…”
Section: Incisor Transit-amplifying Cellsmentioning
confidence: 99%
“…The transit-amplifying cells are the most rapidly cycling cells in the incisor pulp and they are located immediately distal to the slowcycling stem cells (Lapthanasupkul et al, 2012). These cells express specific genes, most notably those of the polycomb repressive complex 1 (Prc1), that are generally not expressed in the surrounding cells and which are important for cell proliferation (Lapthanasupkul et al, 2012). Targeted deletion of genes integral to Prc1, such as Ring1a (Ring1) and Ring1b (Rnf2), results in the arrest of incisor growth and loss of transit-amplifying cells, suggesting that a functional Prc1 complex is essential to maintain proliferation in these cells.…”
Section: Incisor Transit-amplifying Cellsmentioning
confidence: 99%